Self Reliance and homelessness in Australia: Challenges of definition, conceptualisation and measurement - Kunnen, Nola; Martin, Robyn (AHURI, 2005)
What is self-reliance? More specifically, can it be defined and measured among people who are homeless, at risk of becoming homeless and accessing related support services? These challenges were the focus of research undertaken in Western Australia in 2003-2004. This paper informs policy and program debate on responses to homelessness as well as housing and welfare. The promotion of client self reliance is emphasised as an outcome of the Supported Accommodation Assistance Program (SAAP). The task of defining self reliance and assessing its attainment among people who have been or remain homeless is problematic as most journeys through homelessness are characterised by complexity, instability and non-uniformity. Client experiences of homelessness and crisis are multidimensional and shaped by context, history and culture. This presents a major challenge in defining, establishing and making visible people’s attempts at and progress towards self reliance. Program administrators, policy makers, service providers and other interested stakeholders identify that the transparent measurement of this complex phenomenon is challenging yet should be attempted in some form. This paper reports on research undertaken in Western Australia in 2003-2004 which focussed on defining, measuring and contextualising self reliance in homelessness service systems. The paper focuses on experiences that illustrate the challenges and complexities of researching and conceptualising self reliance among recipients of SAAP services.